Analisis Kemampuan Membaca Cepat Pada Mahasiswa Tingkat II Program Studi Pendidikan Bahasa Jepang Universitas Riau Tahun Ajaran 2014/2015 - Indra Irawan; Sri Wahyu Widiati; Merri Silvia Basri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abtract: Speed reading is a blend of speed reading with understanding thecontent of reading. This study aims to determine the level of reading speed, readingcomprehension, effective speed reading, and speed reading constraints in Japanese.This study used quantitative research methods. Reading speed is calculated based wpm(words per minute). texts are used to measure the student reading speed were about theJapanese language proficiency test (nihongo ryoku shiken) N4 (level 4). Samples of thisstudy were the students of level 2 of Japanese Study Program,FKIP University of Riauacademic year 2014/2015 academic year consisted of 29 people. The results of the studyare the average of speed of reading students in the amount at 155 wpm (words perminute), which means speed reading of students categorized slow readersas,understanding of reading students gained an average value at 55.86, which means theability of understanding of students categorized as sufficient and effective studentsspeed reading amounted to 106 wpm (words per minute), which means that the readerhas not been effective. It was caused by several factors, including the ability of readingis still stammering, reading strategies only read text, there were kanji and katakana onreading, and did not understand the meaning of the word in texts.Keywords: reading, speed, comprehension, effective, dokkai, N4